Salmonella spp. em carne bovina in natura resfriada e embalada a vácuo : ocorrência e perfil de resistência antimicrobiana - Müller, Barbara (2018)
Brazil is currently the second largest producer and the first beef exporter, with Mato Grosso being the first State in the ranking of cattle slaughter in the country with 15.4% of the national share. In order to maintain this growing production and exportation of Brazilian beef, it is necessary that the quality of the product is within the established standards and legislation, especially with regard to contamination by food pathogens. Among the main microorganisms involved in outbreaks due to Foodborne Diseases, Salmonella spp. Stands out, being frequently associated with contamination of bovine meat around the world, provoking many cases of salmonellosis in outbreaks by Foodborne Diseases. This fact in association with the use of antibiotics in animal production as a therapeutic treatments creates new challenges to prevent and to control infections with Salmonella spp. resistant to multiple medications, which difficult the treatment of diseases caused by this pathogen. In this context, the present study aimed to estimate the occurrence of Salmonella spp. in fresh beef and to evaluate the antimicrobial resistance profile of the isolates. A total of 107 beef samples produced in Mato Grosso were submitted to microbiological analysis, PCR for isolation and identification of Salmonella spp. and characterization of the antimicrobial susceptibility profile and genotypic profile of each strain. The occurrence of Salmonella spp. was verified in 5.6% (6/107) of the samples and all strains were resistant to multiple drugs, and with different genotypic profiles. These evidences can cause difficulties in the treatment of diseases caused by Salmonella spp., generating negative impacts to public health besides economic damages by the embargo of beef contaminated by this pathogen.